DEVELOPMENT OF CAN PASTEURIZATION WITH REFERENCE TO CONTINUOUS OPEN TYPE APPARATUS - K. R. Gammatsaev; L. R. Ibragimova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In the paper are considered the problems connected with the development of scientifically valid can pasteurization regimes in the self-exhaustion tare in continuous open type apparatus operating under atmosphere pressure. By the results of carried out researches is established that the use of ‘breathing’ type allows to reduce apparatus time of thermal treatment on average 25% provided the achievement of necessary lethality of pasteurization regimes.